2021
DOI: 10.1371/journal.pone.0254419
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation in Lebanon “What do we have”? A national survey among chest physicians

Abstract: Background Pulmonary rehabilitation (PR) is not very often used by physicians in Lebanon despite evidence on its positive effects on health-related quality of life. Aim This study assesses the knowledge, attitudes and practices of PR among physicians in Lebanon. In addition, the study identifies the main barriers to access to PR according to chest physicians. Insight into these issues will help to increase awareness about the need for PR programs and can contribute to designing such programs in the country. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Several studies conducted have demonstrated the importance of the role played by the PT in the promotion of CR. PT act as a bridge between patients and other healthcare professionals, and this has been confirmed by diverse findings and has been recommended by international guidelines and the WHO [ 5 ] and is highlighted by our results. PT’s qualifications and their ability to screen, diagnose, and provide appropriate treatment or referral have positioned them as important providers of quality health care within the primary care team [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies conducted have demonstrated the importance of the role played by the PT in the promotion of CR. PT act as a bridge between patients and other healthcare professionals, and this has been confirmed by diverse findings and has been recommended by international guidelines and the WHO [ 5 ] and is highlighted by our results. PT’s qualifications and their ability to screen, diagnose, and provide appropriate treatment or referral have positioned them as important providers of quality health care within the primary care team [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…The PT roles include health education, direct interventions, research, advocacy, and collaborative consultation [ 5 ]. PT plays a major role in this according to the American Physical Therapy Association and World Confederation of Physical Therapy (WCPT) [ 3 , 4 ]: first, in the management of the diseases and, second, in the overall health promotion of the population.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with a Lebanese study which attributed lack of patient referral to PR by chest physicians to absence of awareness and education about PR. 37 Consequently, the lack of awareness of PR benefits or value translates into under-funding or under-resource allocation for the service. This is not surprising because LMIC governments have restricted budgets and must prioritise investment in healthcare interventions that are perceived https://doi.org/10.2147/COPD.S348663…”
Section: Discussionmentioning
confidence: 99%
“…Te signifcance of the function played by the PT in the promotion of CR has been shown by numerous studies. Te role of PT in bridging the gap between patients and other healthcare providers has been supported by a number of fndings, is advocated by worldwide guidelines and WHO, and is underlined by our results [17]. PTs are signifcant contributors to the primary care team as vital providers of high-quality healthcare due to their credentials and capacity to screen, diagnose, and prescribe the proper treatment or referral [18].…”
Section: Discussionmentioning
confidence: 68%